Dialogando com o desenho: interações no processo de construção imagética da criança no 5º ano do ensino fundamental. - Nacari, Déborah Provetti Scardini (2011)
In the historical-cultural perspective, the drawing is processed by means of a shared and complex way, under some diverse relations with the other and with the immersed signs of the culture. That is, something constituted by the social interactions and that can modify the structure of the psychological functions, therefore as socialized sign, propitiates the incorporation of the functions socially. In this way, the figuration carrier sensitive and established meanings historically, showing the shared experiences and the ways of the subject to think and perceive the world. Such reflections gave shape to the main problem of this research: which interactions can be detected in the (re) construction of the children‟s imaginary of 5th year of elementary school? Under such perspective, this work deals with the interactions in the production process of the drawing of children context of teach-learning of the elementary school having as goal: anal to analysis, through design, experiences and content internalized over the construction of child‟s knowledge (in special the city of Vitória-ES/Brazil) to 5th year of elementary school, to compare the drawings of children who live different realities in Vitória-ES/Brazil: shapes, colors, signs. For its accomplishment, it was opted for the construction process based in the qualitative investigation by the fact to propitiate negotiations, sharing and confrontation of the ideas, becoming possible a joint construction of the knowledge. For this research, the researcher and the involved children, become themselves into co-authors of the context studied. As locus of the research, it was chosen two classes of 5th year of elementary school. One of then, with 29 students, from Municipal School José Lemos de Miranda (São Pedro, in Vitória, ES-Brazil). This school was chosen because it is inserted in a poor place, in 26 Vitória-ES/Brazil; and the other school, with 32 students, of Sagrado Coração de Maria School (Praia do Canto, in Vitória-ES/Brazil), was chosen because it is inserted in a middle-class of neighborhood. In the process of research, it was perceived that the children with the support of the verbal language formulates meanings on the seen and imagined object, printing lines and forms that if overlap to the physiological aspects of the visual perception. That is, the drawing discloses a reality appraised, enriched for the picked up vision of the image, but the meanings established for the author, or observer who becomes it perceivable and identified. In the systemizing situations, it was observed that the teaching-learning process of drawing, implies a co-construction between teachers and learners. And, moreover, the necessity to interlace emotion and cognition that foment drawing experiences, whose process concurs for the imaginative reconstruct of the apprentices.